2011
DOI: 10.1007/s00586-011-2029-6
|View full text |Cite
|
Sign up to set email alerts
|

Spinous process morphology: the effect of ageing through adulthood on spinous process size and relationship to sagittal alignment

Abstract: This study demonstrates that the dimensions of the LSP change with age. Increases in LSP height and even more impressive increases in LSP width occur with advancing age. There is an inverse relationship between lumbar lordosis and LSP height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 14 publications
2
51
0
1
Order By: Relevance
“…Our hypothesis explaining the result of the increased heights of the L4 and L5 spinous processes with age may be a secondary adaptive response to increase their mechanical properties after sharing a compressive load from anterior structures, according to Wolf's Law [1,9]. Because we found that the spinous process height was increased after the intervertebral disc space narrowed and the vertebral body height was decreased, we think that the adaptive response occurred to act as a tethering structure to prevent hyperextension of the lumbar spine and to increase the stiffness and stability.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Our hypothesis explaining the result of the increased heights of the L4 and L5 spinous processes with age may be a secondary adaptive response to increase their mechanical properties after sharing a compressive load from anterior structures, according to Wolf's Law [1,9]. Because we found that the spinous process height was increased after the intervertebral disc space narrowed and the vertebral body height was decreased, we think that the adaptive response occurred to act as a tethering structure to prevent hyperextension of the lumbar spine and to increase the stiffness and stability.…”
Section: Discussionmentioning
confidence: 90%
“…However, some literature published in English mentions changes in spinous process morphology with age [9,10]. Aylott et al [9] measured the height and width of lumbar spinous processes with CT and showed significant increases that were correlated with age. Their study also showed a negative correlation between the height of the spinous processes and the degree of the lumbar lordosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations